A randomised controlled trial of multiple periods of outdoor free-play to increase moderate-to-vigorous physical activity among 3 to 6 year old children attending childcare: study protocol. (December 2016) - Wolfenden, Luke; Wiggers, John; Morgan, Philip; Razak, Lubna; Jones, Jannah; Finch, Meghan; Sutherland, Rachel; Lecathelinais, Christophe; Gillham, Karen; Yoong, Sze
Abstract Background The implementation of physical activity interventions in centre-based childcare services has been recommended to improve child health. This study aims to evaluate the efficacy of scheduling multiple periods of outdoor free play in increasing the time children spend in moderate-to-vigorous physical activity (MVPA) during childcare. Methods The study will employ a between group cluster randomised controlled trial design. Fourteen childcare services in the Hunter New England region of New South Wales, Australia, who currently implement a single session of free outdoor play between their core operational hours of 9 am to 3 pm will be recruited into the trial. Childcare services will be randomised to an intervention or a no intervention control group. Childcare services in the intervention group will be supported by an early childhood education specialist to provide three periods of outdoor free play for children between the hours of 9 am to 3 pm. Each period of outdoor free play will be at least 15 min in duration but must equate to their total usual duration of outdoor play. Services in the control group will continue to implement a single period of outdoor play. The primary trial outcome is minutes of time children spend in MVPA whilst in care assessed objectively via accelerometer over 5 days. Outcome assessment will occur at baseline and 3 months post baseline. Generalised Linear Mixed Models (GLMM) under an intention to treat framework will be used to compare differences between groups in the primary trial outcome at follow-up. Sensitivity analysis will be conducted to test assumptions of missing data. Per protocol analysis will be performed using services that implemented the intervention as intended and subgroup analysis undertaken by gender and baseline physical activity levels of children. Discussion The study tests a simple ecological intervention that has the potential to increase child physical activity in care. Trial registration Australian New Zealand Clinical Trials Registry12616000347460 . Prospectively registered 17th March 2016.